Human Resource Management (HRM) - Ediarman Ediarman; Sri Langgeng Ratnasari; Ervin Nora Susanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of understanding and implementing human resource management (HRM) on individual performance effectiveness. The research approach used is quantitative descriptive-verification with data collection through a Likert-scale questionnaire. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (SEM-PLS) to test the relationship between latent variables. The results show that HRM understanding has a positive and significant effect on HRM implementation, and HRM implementation has a significant effect on individual performance effectiveness. In addition, HRM understanding has an indirect effect on performance effectiveness through HRM implementation as a mediating variable. These findings emphasize the importance of increasing individual literacy and competence in understanding HRM principles to improve performance sustainably. This study provides theoretical contributions to the development of a competency-based HRM performance model and offers practical implications for organizations to strengthen training and integrated HRM management systems